2010
DOI: 10.1002/dmrr.1036
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly high rates of obesity and dysglycemia among villagers in Cameroon

Abstract: Our survey in Cameroon recorded obesity and dysglycemia in inhabitants, which are similar to those reported elsewhere in the region. Typically these metabolic disturbances are attributed to the adoption of a new urban lifestyle including diminished physical activity and an altered ('Western') diet. Unexpectedly we found that, like urban populations, our rural population had high rates of metabolic disturbances, despite living in villages and being physically active and consuming traditional diet that is high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…We have recently shown a high prevalence of diabetes and obesity in a rural area of Cameroon, confirming that even in a setting with a protective environment, diabetes is an important and neglected health problem [12]. In fact, most patients were unaware of having diabetes and none was on a regular treatment.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…We have recently shown a high prevalence of diabetes and obesity in a rural area of Cameroon, confirming that even in a setting with a protective environment, diabetes is an important and neglected health problem [12]. In fact, most patients were unaware of having diabetes and none was on a regular treatment.…”
Section: Introductionmentioning
confidence: 67%
“…A subgroup of 49 patients with diabetes were part of a previous survey [12] and were re-evaluated for the present study. In comparison, significant decrease in terms of fasting glucose (226.5±17.5 vs 182.5±12.6, p 0.04) and a slight, not significant reduction in body weight (77.4±3.1 vs 72.1±2.3) was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full texts of the remaining 76 records were scrutinized for eligibility, among which 50 were excluded. In the end, 26 studies were retained for meta‐analysis (Supporting Information Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…However, assessing nutritional and lifestyle risks in SSA has been difficult because of methodological limitations, such as cultural differences, classification of food groups, and imprecise collection of information [68]. Despite these shortcomings on nutrition and lifestyle assessment, studies focusing on food habits need to be undertaken in SSA given that a recent study by Napoli et al [69] in Cameroon showed unexpectedly high rates of obesity and dysglycaemia among the rural population. This is contrary to the belief that this is the case in the urban settings.…”
Section: Transitions: Nutrition and Lifestylementioning
confidence: 97%